2023
DOI: 10.3390/nu15040992
|View full text |Cite
|
Sign up to set email alerts
|

Avenanthramide Improves Colonic Damage Induced by Food Allergies in Mice through Altering Gut Microbiota and Regulating Hsp70-NF-κB Signaling

Abstract: Food allergies can cause intestinal damage that can exacerbate allergic symptoms, and gut microbiota have been shown to influence allergic development. This study was intended to investigate the effects of Avenanthramide (AVA) on colonic damage induced by food allergy and its mechanism. In Exp. 1, AVA administrations alleviated colonic inflammation in mice challenged with ovalbumin, as shown by decreased concentrations of TNF-α, IL-25 and IL-33. Additionally, the AVA supplementations improved intestinal barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Therefore, it is worth investigating the changes in typical microorganisms caused by FA in different experimental settings. According to recent studies, Lachnospiraceae_NK4A136_group is a potential probiotic involved in the Hsp70‐NF‐κB signaling to ameliorate colonic damage and inflammation caused by FA (Liu et al., 2023). Alistipes could produce indole, succinic acid, and a small amount of acetic and propionic acids, which increases the expression of tight junction proteins and downregulates the expression of proinflammatory cytokines to enhance the intestinal barrier and reduce diarrhea (Parker et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is worth investigating the changes in typical microorganisms caused by FA in different experimental settings. According to recent studies, Lachnospiraceae_NK4A136_group is a potential probiotic involved in the Hsp70‐NF‐κB signaling to ameliorate colonic damage and inflammation caused by FA (Liu et al., 2023). Alistipes could produce indole, succinic acid, and a small amount of acetic and propionic acids, which increases the expression of tight junction proteins and downregulates the expression of proinflammatory cytokines to enhance the intestinal barrier and reduce diarrhea (Parker et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate promoted IL-22 generation by CD4 + T cells through G protein-coupled receptor 41 to relieve intestinal inflammation [46] . Alistipes and Lachnospiraceae_NK4A136_group were expressed at lower levels in both OVA and peanut allergic mice [22,40,45] .…”
Section: A-c)mentioning
confidence: 98%
“…In addition, Lachnospiraceae_NK4A136_group belonging to the Lachnospiraceae family was commonly thought to be involved in intestinal mucosal barrier protection and immune regulation because of its capacity to produce butyrate [45] . Butyrate promoted IL-22 generation by CD4 + T cells through G protein-coupled receptor 41 to relieve intestinal inflammation [46] .…”
Section: A-c)mentioning
confidence: 99%
“…Plant polyphenol is a kind of secondary metabolites with phenol structure and can dynamically interact with intestinal bacteria, playing a crucial role in maintaining intestinal health in animals 13 . Polyphenols can directly regulate the composition and diversity of gut microbes, increase the number of beneficial bacteria in the intestine, and thus improve the microbial balance within the intestine 14 . Our previous finding suggested that grape seed proanthocyanidin (GSP), a natural polyphenol compound, changed the intestinal microbial structure and thus activating the intestinal farnesoid X receptor (FXR) signaling pathway to prevent intestinal inflammation in rodent animal models 15 .…”
Section: Introductionmentioning
confidence: 99%
“…13 Polyphenols can directly regulate the composition and diversity of gut microbes, increase the number of beneficial bacteria in the intestine, and thus improve the microbial balance within the intestine. 14 Our previous finding suggested that grape seed proanthocyanidin (GSP), a natural polyphenol compound, changed the intestinal microbial structure and thus activating the intestinal farnesoid X receptor (FXR) signaling pathway to prevent intestinal inflammation in rodent animal models. 15 However, there are few reports about the application of polyphenols in dogs, and the relationship between GSP and canine gut microbiota requires further exploration.…”
Section: Introductionmentioning
confidence: 99%